Learn Generative AI with PyTorch - Liu, Mark (Manning Publications, 2025)
Learn Generative AI with PyTorch introduces the underlying mechanics of generative AI by helping you build your own working AI models. You'll begin by creating simple images using a GAN, and then progress to writing a language translation transformer line-by-line. As you work through the fun and fascinating projects, you'll train models to create anime images, write like Hemingway, make music like Mozart, and more. You just need Python and a few machine learning basics to get started. You'll learn the rest as you go!
Machine-generated record
Keywords: Artificial intelligence; Machine learning; Python (Computer program language); Intelligence artificielle; Apprentissage automatique; Python (Langage de programmation); artificial intelligence; Audiobooks; Livres audio